Understanding certain Clostridium difficile virulence and antibiotic resistance factors and how these relate to patient clinical outcome - Kinsmore, Natasha Louise (2019)
Clostridium difficile is known for causing the nosocomial diarrhoeal disease, C. difficile infection (CDI). The aim of this study was to investigate the molecular and phenotypic basis of certain C. difficile virulence factors, such as C. difficile transferase (CDT) and sporulation, as well as rifaximin antibiotic resistance, and how these relate to patient clinical outcome.